PENGEMBANGAN PERANGKAT LUNAK PERANCANGAN LAPIS ULANG PERKERASAN LENTUR BERDASARKAN MANUAL BINA MARGA 2017 - Kushari, Berlian; Hidaya, Nur Robbi (Teknisia, 2021)
The Benkelman Beam method is used to design overlay thickness on a flexible pavement based on its maximum rebound deflection representing its structural capacity. This method has been adopted in the 2017 Bina Marga Design Manual applicable for Indonesian road design since June 2017. This research was aimed to develop a tool that can facilitate rebound deflection data analysis and overlay thickness design based on the overlay design curves adopted in the Bina Marga guide. Visual Basic 6.0 was used as the environment for the development. In addition to the standard curves, the tool added four intermediate curves corresponding to the design load of 7.5x106, 3.5x106, 1.5x106, and 0.75x106 ESALs to enable more economical designs. Furthermore, a manual overlay procedure was conducted using overlay data from Sampaan – Singosaren, Kowangan – Maron, and Imogiri Barat road sections to validate the usability of the developed tool. The validation showed an acceptable difference of less than 2% between results obtained from the software and the manual calculations.